Neuromuscular Disorders - Zaher, Ashraf (IntechOpen, 2012)
Neuromuscular Disorders is an interesting compendium of diverse and fairly inclusive topics in disorders of nerve and muscle, with a spectrum of generally well written and pertinent chapters referencing specific categories of neuromuscular diseases. The expected emphasis on understanding the implications, diagnosis and treatment of the specific muscle and nerve diseases is well done. It contains a basic introductory chapter which is very well-done, and a large range of topics, well-summarized, making it a good reference manual as well as an aid to diagnosis and treatment contained in a relatively small volume. Its accessibility on the internet may make it especially appealing to the younger of us, making it simple to access without necessitating the book's presence in the office.